PARTISIPASI PEREMPUAN DALAM PROGRAM KAMPUNG IKLIM (PROKLIM) (Studi Kasus di Dusun Palasari Desa Sukahurip Kecamatan Cihaurbeuti Kabupaten Ciamis) - Ilma Khoiruumah; Ahmad Hamdan; Bayu Adi Laksono (Disaster Research Center, Universitas Sebelas Maret, Surakarta, Indonesia, 2024)
One of Indonesia's current development sectors is climate change control. Program Kampung Iklim was created, so that communities at the site level can carry out adaptation, mitigation, and institutional actions & sustainable support. Palasari hamlet is a ProKlim hamlet, but has low participation from the female population, so that achieving program sustainability is slightly hampered. The purpose of this study was to determine women's participation in the Program Kampung Iklim. The method used in this research is a case study with data collection through interviews, observation, and documentation. The results showed that women's participation went through 4 stages, (1) women's participation in ProKlim planning, including response participation such as asking questions in socialization activities and participation of tools and materials. (2) Women's participation in the implementation of ProKlim, there is participation of support, there is also participation of expertise and labor. (3) Women's participation in the utilization of ProKlim results, there is an increase in knowledge because it is reflected in the skills in utilizing yard land to improve food security. (4) Women's participation in the evaluation of ProKlim, namely by giving opinions/responses when the activities/programs have been implemented. ProKlim is a series of processes using the principle of empowerment, with the aim of reducing greenhouse gas emissions to create prosperity.